Treatment side affects exercising microvascular oxygenation response in active breast cancer survivors: A pilot study. (20th November 2022) - Cayot, Trent E.; Herbert, Brooklyn; Klika, Riggs J.
Abstract: Cancer treatment is associated with cardiovascular toxicity, skeletal muscle dysfunction and interruptions in mitochondrial respiration. Microvascular oxygenation responses, measured via near‐infrared spectroscopy (NIRS), at peak exercise intensity has previously been associated with aerobic capacity. Specifically, the greater magnitude of microvascular deoxygenation observed at peak exercise intensity has been associated with higher aerobic capacity. Therefore, a pilot study investigated if diagnosis side (uninvolved side, treatment side) and/or exercise side (paddle side, non‐paddle side) affected microvascular oxygenation responses at peak intensity during paddle exercise. Thirty‐three breast cancer survivors (age = 57 ± 9 years, height = 1.64 ± 0.05 m, weight = 76.5 ± 15.6 kg, 7 ± 7 years since treatment) who also competed as dragon boat racers performed a unilateral (paddle), discontinuous graded exercise test (2‐min exercise, 1‐min rest) on a rowing ergometer to volitional fatigue. Tissue oxygenation saturation (StO2DIFF ) and total haemoglobin concentration (total[heme]DIFF ) responses at peak exercise intensity were measured bilaterally from the posterior deltoids using NIRS. Two‐way analysis of variance determined if diagnosis side and/or exercise side effected StO2DIFF or total[heme]DIFF . Diagnosis side elicited a moderate effect (effect size = 0.66) on StO2DIFF, as the treatment side deoxygenated less (−6.0 ± 14.7 ∆BSL) compared to the uninvolved side (−16.9 ± 16.9 ∆BSL) at peak exercise intensity. No other significant main effects or interactions were observed for StO2DIFF or total[heme]DIFF . The pilot findings suggest that the ability of the exercising muscle to use oxygen for the purpose of mitochondrial oxidative respiration may be impaired on the treatment side.